Farmers adopt healthy rice seedling practices in Bangladesh - CGIAR Research Program on Rice (2017)
Awareness-raising activities through a 10-minute instructional video by the CSISA project (Cereal Systems Initiative South Asia) in Bangladesh resulted in 60,000 hectares planted with healthy rice seedlings in 2017, while direct training resulted in an additional 28,300 hectares planted under healthy rice seedling techniques